Kesadaran Berempati Terhadap Perundungan Melalui Storytelling pada SDN 10 Tanjung Lago - Hurriyati, Dwi; Mega Wulansari (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This Community Service Program aims to enhance students' empathetic awareness of bullying behavior at SD Negeri 10 Tanjung Lago through the storytelling method. Based on initial observations, a phenomenon of playful teasing was found, which students often misinterpret, indicating low awareness of the psychological impact of such actions. The intervention was carried out in three main stages: (1) interactive storytelling using the educational comic